Making Federalism through Law: Regulating Socio-economic Challenges of Energy Development, a Case Study of Alberta’s Oil sands and the Regional Municipality of Wood Buffalo - Thompson, Chidinma Bernadine (Graduate Studies, 2013)
Socio-economic challenges of large scale oil and gas development, especially oil sands, within municipal boundaries are not given adequate attention in Alberta’s oil and gas development regulatory framework. There is no forum in the framework that allows a thorough consideration and proactive resolution, by responsible governments, of socio-economic challenges of large scale energy development prior to, or at the time of, project approvals. The jurisdiction of municipal authorities to regulate such development is highly circumscribed. None of the recently adopted initiatives by the province seems to have closed this gap in the regulatory framework. The gap exists because Alberta’s oil and gas regulatory framework adopts the unitary model of governance. Given the critical role of public infrastructure and services in energy resource development, the thesis recommends a reform of Alberta’s legislative and regulatory framework for energy development using federalism and its underlying principle of non-centralization. The thesis recommends a suite of non-centralized intergovernmental mechanisms which can conveniently fit into the regulatory framework and anchored in the energy legislative scheme. Using legally-mandated intergovernmental partnerships, Alberta can proactively obviate severe growth pressures, crippling demands on public infrastructure and services, lower quality of life for workers in the host areas, difficulty in attracting and retaining a workforce, and greater risk to energy resource development and huge private investment. A weather-proof regulatory framework with built-in, federal fail-safe mechanisms that enable energy development projects while preserving the wellbeing of host communities is sine qua non to achieve Alberta’s ambitious global energy leadership goals.